Relationship between dietary patterns and mild cognitive impairment (MCI) in elderly women - Alavi-Naeini, Amirmansour; Bagheri, Mahtab; Mirzaei, Kadijeh; Maljaei, Mohammad Bagher; Yekaninejad, Mir Saeed; Yazdani, Alireza (Progress in Nutrition, 2019)
Context: Mild cognitive impairment (MCI) is a transitional stage in cognitive performance between changes seen in normal aging and those observed in dementia. Early diagnosis and intervention during the initial stages of mild cognitive impairment can delay or prevent the onset of dementia. Preventive behavioral interventions, for instance changes in dietary patterns, can play a major role in reducing the burden of this disease. Aim: The aim of this study was to determine the association between dietary patterns and MCI in the elderly. Methods and material: The present case-control study was performed on 82 cases and 163 controls constituted by 60 year-old or older women. We conducted interviews and completed a general questionnaire, IPAQ, FFQ, and MMSE. We used factor analysis and principal component analysis to derive dietary patterns and the chi-square test, independent t-test, and logistic regression to analyze the data. Results: There were significant differences between the two groups in terms of educational level (P = 0.033), employment (p = 0.001), and the number of minutes of study (P =0.020). We identified three dietary patterns including unhealthy, Western, and healthy dietary patterns. There was a statistically significant difference between the two groups only in terms of the healthy dietary pattern (P = 0.004). The odds ratio of developing MCI in people who were in the highest tertile of the healthy dietary pattern was 50% lower than those in the first tertile (OR=0.496, 95%CI: 0.261, 0.943). Conclusion: Our present study demonstrated that only the healthy dietary pattern was significantly associated with MCI and reduced the risk of the disease. It is recommended that further prospective studies be conducted to find more robust relationships.